دور مؤسسات المجتمع المدني في تعزيز مبادئ المواطنة البيئية - الذهبي, إبراهيم; بن عمار, أشواق (جامعة الوادي - University of Eloued, 2021)
تعمل مؤسسات المجتمع المدني في إطار حماية البيئة وتعزيز المواطنة البيئية لدى المواطنين بتزويد كافة المعلومات المتعلقة بالبيئة، بهدف التعرف على الأخطار البيئية ومن ثم السعي إلى توخيها، من اجل تعميم الثقافة البيئية والوعي البيئي من خلال إدراك مدى خطورة المشكلات البيئية وكيفية المشاركة في حلها، وبالتالي ضمان صحة المواطن ببيان الأسباب الرئيسية للأضرار التي تهدد الإنسان وبيئته، ويكون ذلك عن طريق حملات التوعية على مستوى مختلف الشرائح فكلما كان الوعي البيئي مرتفع لدى المواطن تم ترسيخ وتنمية فكرة المواطنة البيئية ومسح فكرة الاستغلال عن طريق تعزيز عن الثقة لدى المواطن والآخرين على حد سواء للاقتداء بعضهم البعض، وهذا ما يخلق ما يسمى بالمواطنة البيئية التي من خلالها يتم ترشيد سلوك المواطن للحفاظ على المصادر البيئية وحماية المحيط البشري. Civil society organizations work within the framework of protecting the environment and promoting environmental citizenship by providing all information related to the environment, with the aim of identifying environmental hazards and then seeking to pursue them, in order to popularize environmental culture and environmental awareness by recognizing the seriousness of environmental problems. And how to participate in solving it, and thus ensuring the health of the citizen by stating the main causes of the damage that threaten sins human beings and their environment, and this is through awareness campaigns at the level of different segments, the higher the environmental awareness among the citizen, the more the idea of environmental citizenship has been consolidated and developed and the idea of exploitation is erased. By promoting the confidence of citizens and others alike to follow each other's example, this creates the so-called environmental citizenship through which citizen behavior is rationalized to preserve environmental resources and protect the human environment.
The role of civil society institutions in promoting the principles of environmental citizenship
مقال
Keywords: المجتمع المدني، المواطنة، البيئة، المواطنة البيئية; Civil Society, Citizenship, Environment, Environmental Citizenship.